Effect of Probiotic on Beneficial and Pathogenic Microorganisms in the Gastrointestinal Tract of Commercial Broiler with BCRDV Vaccine - Islam, MR; Mostofa, M; Mondal, KS; Roy, RR; Sorwar, MG; Islam, S (Progressive Agriculture, 2014)
The present study was conducted to determine the effect of probiotic on beneficial and pathogenic microorganisms in the gastrointestinal tract of Commercial Broiler. A total of 80 day-old broiler chicks were divided into two main groups I and II with 40 chicks in each. Group I was supplemented with Probiotic (Saccharomyces cerevisiae 2 gm/kg feed) containing feed and chicks of group II was supplemented with conventional feed. Group I and II was again subdivided into two subgroups as group A, B and C, D respectively on 6 days of age. Birds of subgroups A and C were vaccinated with ND vaccine (BCRDV) and birds of subgroups C and D were kept as unvaccinated. The result evidenced the following information: (a) The total viable count (TVC) and total coliform count (TCC) were significantly (P<0.01) lower in experimental birds as compared to control at 14, 28 and 32 days of age both in vaccinated and non-vaccinated birds. It was always found that the lower TVC in probiotic fed broilers as compared to conventional fed broilers (b) The total lactobacilli count (TLC) was significantly (P<0.01) higher in experimental birds as compared to control at 14, 28 and 32 days of age both in vaccinated and non-vaccinated birds. So it can be said that Saccharomyces cerevisiae supplementation can reduce the pathogenic microorganism and increase the growth of beneficial microorganism. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19111 Progress. Agric. 24(1&2): 107 - 115, 2013